COMPARATIVE ANALYSIS OF XML AND JSON USING PHP APPLICATION PLATFORM WITH REPRESENTATIONAL STATE TRANSFER ( REST ) ARCHITECTURAL - Saryanto, Saryanto; Sumarsono, Sumarsono; Retnowati, Nurcahyani Dewi (Compiler, 2013)
Data communication in the internet today is so complex as an example of the speed factor becomes very important in communicating, everyone wants fast data communication services provided in order to maximum. In relation to the application as a communication liaison with client server applications, web service using a data serialization format to transmit the data. Before the data is sent, either fromthe client to the server or vice versa, should be modified in a specific data format beforehand according to the web service is used. Types of data serialization format used in the web service such as XML and JSON. The method used for testing include data serialization method, data measurement method and data parsing method. Data serialization method is used to calculate the time serialization of data from the database to the form of XML and JSON in applications with PHP platform. Data measurement method used to measure the size of the XML and JSON data which based on many fields of data serialization process. Data parsing method is used to calculate the processing time and JSON parsing XML data. Results o f comparative analysis o f XML and JSON in PHP applications using thearchitecture Rest can be concluded that the test result o f the difference in time and time serialization and JSON parsing XML data is influenced by the number o f records, if the number of records the greater the difference in eating time data serialization and parsing the data the greater the time also itcan be concluded that the faster the process JSON serialization and parsing XML data is compared. Testing results o f the JSON data size is smaller than the size of XML. Data exchange using XML format has a size limit of up to 31456.31 KB while JSON XML exceeds the size limit. Testing results on the Internet when the number o f records up to 50,000 data when the data serialization and parsing time data can not be detected in the database.